ОБЗОР ЛИТЕРАТУРЫ О ВЛИЯНИИ РАЗЛИЧНЫХ ГАЗОВ НА ЛЕГКИЕ ЧЕЛОВЕКА - Рахмонбердиев Муҳаммаджон Ахмаджон ўғли (TADQIQOTLAR, 2025)
Abstract. Exposure of the lungs to airborne toxicants from different sources in the environment may lead to acute and chronic pulmonary or even systemic inflammation. Cigarette smoke is the leading cause of chronic obstructive pulmonary disease, although wood smoke in urban areas of underdeveloped countries is now recognized as a leading cause of respiratory disease. Mycotoxins from fungal spores pose an occupational risk for respiratory illness and also present a health hazard to those living in damp buildings. Microscopic airborne particulates of asbestos and silica (from building materials) and those of heavy metals (from paint) are additional sources of indoor air pollution that contributes to respiratory illness and is known to cause respiratory illness in experimental animals. Ricin in aerosolized form is a potential bioweapon that is extremely toxic yet relatively easy to produce. Although the aforementioned agents belong to different classes of toxic chemicals, their pathogenicity is similar. They induce the recruitment and activation of macrophages, activation of mitogen-activated protein kinases, inhibition of protein synthesis, and production of interleukin-1 beta. Targeting either macrophages (using nanoparticles) or the production of interleukin-1 beta (using inhibitors against protein kinases, NOD- like receptor protein-3, or P2X7) may potentially be employed to treat these types of lung inflammation without affecting the natural immune response to bacterial infections.